SEJARAH TRANSPORMASI SYARIAT ISLAM KEDALAM HUKUM NASIONAL - Gunawan, Syafri (IAIN Padangsidimpuan, 2020)
This paper outlines the phases after the Islamic law in Indonesia, so in this paper the focus of the main problem is how to transform Islamic law into positive law in Indonesia. To answer this main issue, it will be divided into sub-headings about the period of acceptance of Islamic law in Indonesia, the bleak period of Islamic law in Indonesia, and the period of enlightenment of Islamic law to make part of the main alternatives in national law. In order to answer this main problem, the author uses the method of literature study by tracing classic books and books as well as other references relating to the history of Islamic law reformation in Indonesia.This paper outlines the phases after the Islamic law in Indonesia, so in this paper the focus of the main problem is how to transform Islamic law into positive law in Indonesia. To answer this main issue, it will be divided into sub-headings about the period of acceptance of Islamic law in Indonesia, the bleak period of Islamic law in Indonesia, and the period of enlightenment of Islamic law to make part of the main alternatives in national law. In order to answer this main problem, the author uses the method of literature study by tracing classic books and books as well as other references relating to the history of Islamic law reformation in Indonesia.